PROPOSED A COMPACT MULTIBAND AND BROADBAND RECTANGULAR MICROSTRIP PATCH ANTENNA FOR C-BAND AND X-BAND. - Tiwari, Rahul; Verma, Seema (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In this communication two proposed antenna described one for broadband at 6.71445GHz to 11.9362GHz with finite ground plane. The antenna designed with 11.4051mm× 8.388 mm radiating copper patch with ground plane design with 21.0051mm x17. 988mm. And this Compact broadband rectangular shape microstrip patch antenna is designed and analyzed for the return loss of -20.08 dB is achieved at the resonant frequency of 7.941GHz, From Antenna2-it is observed that, antenna for multiband at different frequency. The primary radiating elements are Simple Rectangular Microstrip Patch Antenna in upper side with probe feed and use finite ground plane are two parallel crossed printed slot for three different frequency applications which is smaller in size compared to other available multiband antennas. From the result, it is observed that, the return loss of -16.97 dB is achieved at the first resonant frequency of 4.853GHz, -10.30dB at the second resonant frequency of 8.382GHz, -10.73 dB at the third resonant frequency of 9.265GHz, -17.38 dB at the fourth resonant frequency of 10.15GHz and -12.37 dB at the fifth resonant frequency of 11.91GHz. This broadband and multi-band highly efficient antenna for use in C-Band, and X-Band.